"Man Cannot Exist Alone": The Challenge of Health Care to Honor the Role of Women in Society. (November 2018) - Scrafford, Jonathan
Women's roles in society are changing. While most of those changes recognize and enhance the contributions of feminine ingenuity to human development, some threaten to isolate women physically, socially, and emotionally. Developments in reproductive health care, and the writings of Pope Saint John Paul II, offer lenses by which to evaluate the shifting landscape of women's role in society. On the one hand, practices such as contraception, abortion, surrogacy, and assisted reproductive technologies over time will weaken the physical, social, and emotional bonds that procreation has held between man and woman, parents and children, and families and society. On the other hand, the expansion of different modes of natural family planning and pregnancy support centers offers to preserve those bonds. Summary: Women's role in families, and therefore society, is invaluable. Several approaches to reproductive health offered by medicine may isolate women over time, and some evidences suggest we are already seeing that effect. Other approaches to women's health may be able to preserve the physical, emotional, and social bonds that integrate women to the family, and therefore society.